Effects of Acute Dengue Infection on Sperm and Virus Clearance in Body Fluids of Men - Joffrey Mons (Emerging Infectious Diseases, 2022)
We investigated the effects of dengue virus (DENV) on semen using samples collected 7, 15, 30, 60, and 90 days after symptom onset from 10 infected volunteers on Réunion Island. We assessed characteristics of semen and reproductive hormones and isolated motile spermatozoa from semen. We assayed semen for DENV using reverse transcription PCR and searched for DENV RNA by virus isolation in Vero E6 cell cultures. Four volunteers had >1 DENV RNA-positive semen samples; 2 volunteers had DENV RNA–positive semen at day 15 and 1 at day 30. No motile sperm were DENV positive. After exposure to positive semen, few Vero E6 cells stained positive for DENV antigens, indicating low levels of replicative virus. We found DENV had shorter duration in semen than in blood. These findings support the possibilities that DENV is sexually transmissible for a short period after acute dengue illness and that acute dengue induces reversible alterations in sperm.